Langerhans cell histiocytosis in an infant: a case report from North-East India - Bachaspatimayum, Romita; Yaku, Kago (International Journal of Research in Dermatology, 2020)
Langerhans cell histiocytosis (LCH) is a rare disorder of reticuloendothelial system characterized by uncontrolled proliferation and accumulation of CD1a and CD207 dendritic cells (DCs). 3-4 cases per million occur annually in children under 15 years of age, with a male:female ratio of 2:1 and peak incidence in infants aged 1 to 2 years. Report a case of LCH in a month-old female infant with skin lesions for 2-3 weeks. Skin biopsy was suggestive of LCH and it was confirmed with immunohistochemistry markers that were positive for S100, CD1A and negative for CD68.